Pengaruh Variasi Intensitas Cahaya terhadap Laju Fotosintesis pada Tanaman Caladium melalui Metode Floating Leaf Disk Assay - Gismanda Rosandy; Rina Oktaviana; Fauza Syahro Sobrina (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Photosynthesis is the process of converting light energy into chemical energy which is greatly influenced by light intensity and leaf pigment content. This study analyzed the effect of three light intensities (dark, shade, and bright) on the photosynthesis rate of Caladium plants using the Floating Leaf Disk Assay (FLDA) method. This method measures the photosynthesis rate based on the leaf disk floatation time as an indicator of oxygen formation from the water photolysis process. The study was conducted at the Biology Laboratory, Faculty of Teacher Training and Education, Lambung Mangkurat University, using a quasi-experimental design with 3 repetitions. The results showed that bright conditions provided the fastest floatation time, which was an average of 3.8 minutes with bubble production of 18-22 bubbles/minute. Shade conditions showed a moderate response with a floatation time of 8.6 minutes and 7-10 bubbles/minute. In dark conditions, neither floatation nor oxygen production occurred. Caladiums with full green leaves exhibited higher photosynthetic rates (3.5-4.0 minutes) than variegated ones (5.2-6.1 minutes), reflecting differences in chlorophyll content. These findings confirm that the combination of light intensity and leaf pigment content is a major factor in determining photosynthetic efficiency. The research findings are expected to provide a basis for optimal lighting management in ornamental plant cultivation and serve as contextual teaching materials in biology learning.